2022
DOI: 10.3390/molecules27165316
|View full text |Cite
|
Sign up to set email alerts
|

Walnut Prevents Cognitive Impairment by Regulating the Synaptic and Mitochondrial Dysfunction via JNK Signaling and Apoptosis Pathway in High-Fat Diet-Induced C57BL/6 Mice

Abstract: This study was conducted to evaluate the protective effect of Juglans regia (walnut, Gimcheon 1ho cultivar, GC) on high-fat diet (HFD)-induced cognitive dysfunction in C57BL/6 mice. The main physiological compounds of GC were identified as pedunculagin/casuariin isomer, strictinin, tellimagrandin I, ellagic acid-O-pentoside, and ellagic acid were identified using UPLC Q-TOF/MS analysis. To evaluate the neuro-protective effect of GC, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), 2′,7′-dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Within the Eucalyptus genus, it has been mentioned that they are high in ellagitannins among they are tellimagrandin I, with high antioxidant potential, as is E. globulus with extracts, where the presence of ellagitannins is higher and gives it activity [76]. Furthermore, in extracts of Plinia cauliflora, showed a DPPH inhibitory concentration (IC 50 ) of 1.45 µg/mL ± 0.02 µg/mL, as well as a peroxidation inhibition greater than 70% [77].…”
Section: Antioxidant Effect Of Tellimagrandin Imentioning
confidence: 99%
“…Within the Eucalyptus genus, it has been mentioned that they are high in ellagitannins among they are tellimagrandin I, with high antioxidant potential, as is E. globulus with extracts, where the presence of ellagitannins is higher and gives it activity [76]. Furthermore, in extracts of Plinia cauliflora, showed a DPPH inhibitory concentration (IC 50 ) of 1.45 µg/mL ± 0.02 µg/mL, as well as a peroxidation inhibition greater than 70% [77].…”
Section: Antioxidant Effect Of Tellimagrandin Imentioning
confidence: 99%
“…In another combined in vivo and in vitro experiment, Moon et al [4] showed that walnuts (Juglans regia) could be a potential functional food to improve diabetic cognitive deficits and neuronal impairments. The study found evidence that walnuts inhibit reactive oxygen species production in high-glucose-induced neuronal and hippocampal cells and ameliorate behavioral and memory dysfunction in mice with cognitive impairment induced by a high fat diet.…”
mentioning
confidence: 99%